2000
DOI: 10.3758/bf03211831
|View full text |Cite
|
Sign up to set email alerts
|

Task demands and representation in long-term repetition priming

Abstract: The effects of task demands on the representation of letter strings in long-term repetition priming (LTRP) were explored in two lexical decision experiments. The stimuli in both experiments were words and nonwords, some presented horizontally and some vertically. The only difference between the two experiments was the response required by the participant. In Experiment 1, the participants pressed one of two buttons, indicating whether or not a given stimulus was a word. In Experiment 2, the participants presse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Despite previous demonstrations of size invariance , Srinivas (1996) has shown that priming in picture naming can be sensitive to stimulus size in the context of study and test tasks that require size judgment. Presumably, the task demand in this study made sensitivity to size useful in the context of task performance and resulted in priming that was sensitive to this attribute.Similarly, Johnson (2000) found that changes in word orientation reduced priming when the study task required lexical decision and orientation judgment, but not when the study task required only lexical decision.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite previous demonstrations of size invariance , Srinivas (1996) has shown that priming in picture naming can be sensitive to stimulus size in the context of study and test tasks that require size judgment. Presumably, the task demand in this study made sensitivity to size useful in the context of task performance and resulted in priming that was sensitive to this attribute.Similarly, Johnson (2000) found that changes in word orientation reduced priming when the study task required lexical decision and orientation judgment, but not when the study task required only lexical decision.…”
mentioning
confidence: 99%
“…Not all findings, however, have consistently pointed to a perceptually specific mechanism. Effects of perceptual modifications on priming in word paradigms have been mixed (see Graf & Ryan, 1990, for a review); however, there is evidence that word priming is invariant across perceptual changes barring the use of extremely unusual typefaces or tasks that require scrutiny of perceptual features (Graf & Ryan, 1990;Johnson, 2000). Priming for pictorial stimuli is generally unaffected by a broad range of perceptual manipulations such as changes in size, location, direction of face, color, and illumination (e.g., Biederman & Cooper, 1991a, 1991bCave, Bost, & Cobb, 1996;Cooper, Schacter, Ballesteros, & Moore, 1992).…”
mentioning
confidence: 99%